Synthesis and Crystal Structure Characterization of Zinc (II) Tetronic Acid Complexes - K. C. Prousis; G. Athanasellis; V. Stefanou; D. Matiadis; E. Kokalari; O. Igglessi-Markopoulou; V. McKee; J. Markopoulos (Bioinorganic Chemistry and Applications)
The synthesis and characterization of two new tetronic acid zinc (II) complexes of the empirical formulae [Zn(L–H)2(H2O)2] (1) and [Zn(L–H)2(H2O)(MeOH)]H2O (2) found within the same crystal are reported. The zinc ions bind through alkoxide and carbonyl groups of the ligand 3-methoxycarbonyl-5-phenyl tetronic acid (LH) as indicated by H NMR and X-ray crystallographic studies. These complexes promote intra- and intermolecular interactions, such as hydrogen bonding and π stacking, giving place to the formation of molecular aggregates.